Effects of Audio-Video Listening Comprehension Exercises on Improving Listening Comprehension of Chinese College Students - Wang, Shuhang; Piyanukool, Surachai; Ruangpaisan, Saowarot (BRU ELT JOURNAL, 2025)
The objectives of this quasi-experimental research were 1) to study the effects of audio-video listening exercises on Chinese college students’ listening comprehension skills, and 2) to investigate the students’ level of satisfaction towards listening practice by audio-video listening comprehension exercises. The samples were 30 first year students at Boda College of Jilin Normal University, Jilin Province, People’ s Republic of China. They were selected by Cluster Random Sampling technique. The research instruments consisted of 6 audio-video listening exercises, 6 lesson plans, 40-item listening comprehension tests, and a satisfaction questionnaire. The statistics used to analyze the data were mean, standard deviation, and dependent samples t-test. The study found that 1) the audio-video listening exercises significantly improved students’ listening comprehension; and 2) the level of the students’ satisfaction towards the audio-video listening exercises was at the most satisfactory level.